Limitaciones en la Sustanciación del Proceso Penal en relación a la Suspensión Condicional de la Pena, afecta el Principio de Igualdad ante la Ley - Zhigui Armijos, Luz Marina (2016)
The current juridical research is about “Limitations on the conduct of criminal proceedings in relation to the conditional suspension of sentence, affecting the principle of equality before law”, within the penal environment it tries to give solutions to juridical problems that are given in the Ecuadorian penal system that contains in its catalogue precedents that have lost validity in the current society, being that this particular institution of the conditional suspension of penalty typified in the Comprehensive Organic Penal Code, which allows us to recognize the benefits that are presented for the sentenced. However, as it benefits the inmates, it also becomes a contradiction to constitutional principles, leaving to one side the supremacy of the constitution, only addressing the wording of the rules of the lower rank, breaking the provisions established in the supreme law. Within the concerning questions about the conditional suspension of the penalty that is framed within the field of penal law, there subsists as a creation a constant debate between benefits and right, for which a set of requirements and conditions that have been completed to be conceded, then after they become unavoidable obligations and commitments for the sentenced that if it is not complied with, it should effect the normal penalty without any benefit. This institution that, with necessary justice, recovers today our penal order from 2014, is found to be in doctrinal dispute and the current jurisprudence, specifically referring to the people who were sentenced for a period of over 5 years according to the established procedure, does not have the procedural possibility of applying for it, taking into account that if it is not applied for in the opportune moment it will not be accessible to this benefit, breaching the supreme right of liberty of each human being and juridical security, wasting the circumstances that are offered in the interpretation and application of the principle of equality before the law, essentially in the observation of its exception, equality before the law, a right every human being has, relating in function of the benefit to the sentenced and for the following favorability in the application of the penal norm, a reason which has motivated the study of this topic on our part, with the goal of contributing substantively and procedurally so that our sacred rights can be plainly granted and exercised by the people who really deserve such a benefit, as an intrinsic reality of the current Ecuadorian society.